Impact of abobotulinumtoxinA on the clinical features of cervical dystonia in routine practice. (2020) - Trosch, Richard M.; Misra, Vijay P.; Maisonobe, Pascal; Om, Savary
Abstract: Introduction: The efficacy and safety of abobotulinumtoxinA in the management of cervical dystonia has been established in randomized, controlled trials that use a selected trial population. In this meta-analysis of observational data, we evaluated the real-life effectiveness of abobotulinumtoxinA as delivered in routine clinical practice. Methods: Meta-analysis of patient-level data for adult patients with cervical dystonia treated with abobotulinumtoxinA from three prospective, multicenter, observational studies (NCT01314365, NCT00833196 and NCT01753349 ). Results: We report data for patients treated with abobotulinumtoxinA over one injection cycle at 181 neurology centers in 35 countries. CD clinical features as assessed by Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) Total scores ( N = 920) significantly reduced by a mean [95%CI] of −12.9 [−13.9, −11.8] points at Week 4 ( N = 449) and −3.2 [−3.8, −2.7] points at the end of the injection cycle ( N = 890). All three TWSTRS domains (symptom severity, disability and pain) contributed to the overall improvement. Patients were generally content with symptom control at peak effect of the treatment cycle, with 86% reporting overall satisfaction. Conclusion: Findings from this meta-analysis of observational studies confirm the effectiveness of abobotulinumtoxinA in routine practice. Despite inclusion of a broader population sample, the magnitude of improvements observed is consistent with that seen in the pivotal, randomized controlled trials. Highlights: Observational data provide insights into the effectiveness of aboBoNT-A in practice CD symptoms improve with aboBoNT-A and do not fully return before the next injection Patient satisfaction is highest when aboBoNT-A is given at recommended doses